PENINGKATAN HASIL BELAJAR MATEMATIKA FPB DAN KPK MELALUI MEDIA DAKON MATEMATIKA KELAS IV SDN BOGOREJO KECAMATAN BANCAR KABUPATEN TUBAN - Hikmah, Kholishotul; Fadiana, Mu'jizatin (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
Maths is one of the subjects that plays an important role in education. So far, learning mathematics at the primary school level has mostly been carried out using the lecture method, teachers are reluctant to use learning media, arguing that the use of learning media requires large costs and is not practical. The problem that occurs at SDN Bogorejo, Bancar Subdistrict, Tuban Regency is the low mathematics learning outcomes of students on the material of Greatest Common Factor (FPB) and Least Common Multiple (KPK). This is evident from the implementation of daily tests, the results obtained have not reached the KKM (Minimum Graduation Criteria) determined by the school which is 75. This Classroom Action Research uses the